Automatic alignment and error detection for phonetic transcriptions in the African speech technology project databases - De Villiers, Edward (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.